Dearomatization of a 3-Hydroxypyridine Through an Unexpected Oxidative Deformylation Process: An Entry to Azacyclohexadienones - Mabrouki, Afef; Le Nahenec-Martel, Patricia; Kriaa, Abdelkader; Hedhli, Ahmed; Renard, Pierre-Yves; Sabot, Cyrille (Synlett, 2020)
Phenols are well-known precursors of cyclohexadienones, which have widespread applications in organic synthesis. In contrast, their hydroxypyridine counterparts have not been explored yet. An unprecedented oxidative dearomatization of a 3-hydroxypyridine involving an unexpected deformylation step is reported. The chemical reactivity of the resulting unreported azacyclohexadiene-type compound was also explored.
Keywords: hydroxypyridines; oxidation; hypervalent iodine; phenyliodine diacetate; azacyclohexadienones